2017
DOI: 10.1021/acsami.6b12647
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Peptide-Amphiphile End-Capped Mesoporous Silica Nanoparticles for Tumor Targeting Drug Delivery

Abstract: A tumor targeting redox-responsive drug delivery system (DDS) with bioactive surface was constructed by immobilizing peptide-based amphiphile C12-CGRKKRRQRRRPPQRGDS (defined as ADDA-TCPP) onto the mesoporous silica nanoparticles (MSNs) as an end-capping nanovalve, which consists of two main segments: a hydrophobic alkyl chain ADDA and a hydrophilic amino acid sequence containing a Tat peptide sequence with a thiol terminal group and an RGDS targeting ligand, via a disulfide linkage for redox-triggered intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 47 publications
(86 reference statements)
2
47
0
Order By: Relevance
“…The Benzoic imine bond could be cleaved upon cellular internalization, and pH lowering, and then the disulfide would be accessible by the intracellular GSH for cleavage of doxorubicin cargo delivery . A recent study used large peptide‐based amphiphiles to cover the MSN surface via disulfide linkers, and the hindrance of the linkers prevented their cleavage at 2 µm of GSH, while the release was triggered at 10 × 10 −3 m . Another strategy aiming at hindering the accessibility of disulfides was developed by covalently attaching drugs within the silica mesopores via disulfide linkers .…”
Section: Cargo Loading and Delivery Strategiesmentioning
confidence: 99%
“…The Benzoic imine bond could be cleaved upon cellular internalization, and pH lowering, and then the disulfide would be accessible by the intracellular GSH for cleavage of doxorubicin cargo delivery . A recent study used large peptide‐based amphiphiles to cover the MSN surface via disulfide linkers, and the hindrance of the linkers prevented their cleavage at 2 µm of GSH, while the release was triggered at 10 × 10 −3 m . Another strategy aiming at hindering the accessibility of disulfides was developed by covalently attaching drugs within the silica mesopores via disulfide linkers .…”
Section: Cargo Loading and Delivery Strategiesmentioning
confidence: 99%
“…However, due to inevitable side effects and remarkable toxicity of radiotherapy and chemotherapy, the clinical therapy of nasopharyngeal carcinome encounters the great difficulty. Receptor‐mediated targeting drug delivery nanosystem offered the opportunity to overcome these problems . Studies have reported that, FA (folic acid), an extremely effective targeting molecule, can bind specifically to folate receptors overexpressed in nasopharyngeal carcinoma cells and other tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Drug-loading content (DLC) and drug-loading efficiency (DLE) were determined using equations (1) and 2: DLC=(weight of drug loaded in MSN/weight of MSN)×100% 1DLE=(weight of drug loaded in MSN/weight of feed drug)×100% 2Control MSN-BM/CD-NCApt@DOX was prepared in a similar manner using the scrambled NCApt sequence instead of HApt.…”
Section: Drug Loading and Cappingmentioning
confidence: 99%
“…Conventional cancer chemotherapy encounters drastic limitations in terms of nonspecific delivery of antitumor drugs and severe side-effects. 1,2 A variety of smart drug-delivery systems with selective targeting and controlled release properties have been developed to minimize systemic cytotoxicity. 3 Mesoporous silica nanoparticles (MSN) have been widely used as drug release systems in recent decades due to their desirable properties, including good biocompatibility, high loading capacity and ease of functionalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation